2020
DOI: 10.1042/cs20200193
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RNA-binding protein HuR reduces glomerulosclerosis in experimental nephritis

Abstract: Recent identification of an RNA-binding protein (HuR) that regulates mRNA turnover and translation of numerous transcripts via binding to an ARE in their 3′-UTR involved in inflammation and is abnormally elevated in varied kidney diseases offers a novel target for the treatment of renal inflammation and subsequent fibrosis. Thus, we hypothesized that treatment with a selective inhibition of HuR function with a small molecule, KH-3, would down-regulate HuR-targeted proinflammatory transcripts thereby improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
4
17
0
Order By: Relevance
“…Additionally, Human Antigen R (HuR) also known with its alternative name ELAVL1, is a ubiquitously expressed RBP, which is upregulated and activated under high glucose and in diabetes [ 14 ]. HuR binds to specific domains known as AU-rich elements (ARE) in the 3′UTRs of target genes that play a role in inflammation and diabetic nephropathy [ 15 , 16 , 17 ]. Once it is activated, it translocates to the cytoplasm to bind its mRNA targets affecting their stability and translation [ 18 ].…”
Section: Rbps In the Pathogenesis Of Diabetes And Cardiovascular Diseasementioning
confidence: 99%
“…Additionally, Human Antigen R (HuR) also known with its alternative name ELAVL1, is a ubiquitously expressed RBP, which is upregulated and activated under high glucose and in diabetes [ 14 ]. HuR binds to specific domains known as AU-rich elements (ARE) in the 3′UTRs of target genes that play a role in inflammation and diabetic nephropathy [ 15 , 16 , 17 ]. Once it is activated, it translocates to the cytoplasm to bind its mRNA targets affecting their stability and translation [ 18 ].…”
Section: Rbps In the Pathogenesis Of Diabetes And Cardiovascular Diseasementioning
confidence: 99%
“…C5b-9 formation), Mφ infiltration, pro-inflammatory cytokine and chemokine production all contribute to the renal pathological changes of MsPGN 1 - 3 , 6 , 34 - 36 . As a well-established animal model of MsPGN, Thy-1N pathogenesis is dependent on complement particularly sublytic C5b-9 8 - 12 . Our previous studies have revealed that the production of some pro-inflammatory cytokines and chemokines including IL-6, IL-23, IL-36α, MCP-1 and RANTES was obviously increased in the renal tissues of Thy-1N rats and in the GMCs exposed to sublytic C5b-9 13 - 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Rat Thy-1 nephritis (Thy-1N) is an animal model for studying MsPGN 8 - 10 . Similar to human MsPGN, Thy-1N undergoes complement activation and a series of pathological changes including renal inflammation, GMC proliferation and ECM accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, RNA-seq analysis indicated that compounds were quite selective and did not have a widespread effect on the transcriptome. This discovery opened a new perspective in targeting of RNA primary and secondary structures by chemical compounds as well as inhibiting RNA-protein interactions in human disease [199]. Prior to this, the interaction of small molecules with RNA were extensively studied in viruses.…”
Section: Therapeutic Approaches For Targeting Rna Moleculesmentioning
confidence: 99%